2021
DOI: 10.3390/nursrep11010006
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Factors Affecting Life Satisfaction of the Elderly with Multimorbidity in Korea

Abstract: To enhance the life satisfaction of the elderly with multimorbidity, it is necessary to investigate the relevant factors and to examine the differences in factors according to gender. The aim of this study was to identify factors affecting life satisfaction of the elderly with multimorbidity in the community by gender in Korea. We analyzed data from 2140 participants with multimorbidity who were aged 65 or older and participated in the Korean Longitudinal Study of Ageing (KLoSA) in 2016. A multivariate linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
4
14
1
Order By: Relevance
“…In case of SC/ST group, the female population had shown greater likelihood of life satisfaction than their male counterparts. This corroborates with the findings by Ng et al [ 43 ] and Zhou et al [ 44 ], but contradicts with other studies that reported higher level of life satisfaction among older men [ 45 ]. One of the possible explanations could be the advantage of females in adopting to older age complications than males [ 46 ], who are more impacted by instrumental aspects of life.…”
Section: Discussionsupporting
confidence: 83%
“…In case of SC/ST group, the female population had shown greater likelihood of life satisfaction than their male counterparts. This corroborates with the findings by Ng et al [ 43 ] and Zhou et al [ 44 ], but contradicts with other studies that reported higher level of life satisfaction among older men [ 45 ]. One of the possible explanations could be the advantage of females in adopting to older age complications than males [ 46 ], who are more impacted by instrumental aspects of life.…”
Section: Discussionsupporting
confidence: 83%
“…It con􀅫irms that males and females are similar in life satisfaction. Alternatively, some researchers maintain that there is considerable gender distinction in life satisfaction (Kim, Lee & Dan, 2021;Miao & Bian, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our study goes a step further by examining closely these factors from a gendered perspective; an examination that is virtually non-existent in Ghana. Due to the variations in social norms and biological characteristics, a gendered perspective has been recommended to provide more nuanced information into the associated factors of both men and women's life satisfaction [37][38][39]. The outcome of such attempt has been highlighted by Joshanloo [37] who concluded that sociopolitical, employment-related, and education-related variables were more important to men's life satisfaction whereas women's life satisfaction was associated with variables related to marital status and interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%